Nanosized titania composites for reinforcement of photocatalysis and photoelectrocatalysis - Zahornyi, Maksym (Cambridge Scholars Publishing, 2022)
This book discusses recent advances in the photocatalytic and electrophotocatalytic applications of titanium dioxide nanocomposites containing polymers and other components. These materials possess photocatalytic, virucidal and antimicrobial efficacy and water and air cleaning abilities against eco-toxicants, and allow water splitting for the generation of chemical fuels. The book considers the ability of nanocomposites' components to reinforce titania functionality in photocatalysis and photoelectrocatalysis, and presents an overview of their occurrence in nature, their thermodynamic properti.